2009
DOI: 10.1137/080721662
|View full text |Cite
|
Sign up to set email alerts
|

Families of Sets with Intersecting Clusters

Abstract: A family of k-subsets A 1 , A 2 , . . . , A d on [n] = {1, 2, . . . , n} is called a (d, c)-cluster if the union A 1 ∪ A 2 ∪ · · · ∪ A d contains at most ck elements with c < d. Let F be a family of k-subsets of an n-element set. We show that for k ≥ 2 and n ≥ k + 2, if every (k, 2)-cluster of F is intersecting, then F contains no (k − 1)-dimensional simplices. This leads to an affirmative answer to Mubayi's conjecture for d = k based on Chvátal's simplex theorem. We also show that for any d satisfying 3 ≤ d ≤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Regarding exact results we have already observed that Conjecture 1 holds for d = 2 and d = 3. The only other known case for Conjecture 1 is when d = k, where it follows from an old result of Chvátal[2] (this was recently observed in[1]). E-mail address: mubayi@math.uic.edu (D. Mubayi) 1.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…Regarding exact results we have already observed that Conjecture 1 holds for d = 2 and d = 3. The only other known case for Conjecture 1 is when d = k, where it follows from an old result of Chvátal[2] (this was recently observed in[1]). E-mail address: mubayi@math.uic.edu (D. Mubayi) 1.…”
mentioning
confidence: 76%
“…The only other known case for Conjecture 1 is when d = k, where it follows from an old result of Chvátal[2] (this was recently observed in[1]). E-mail address: mubayi@math.uic.edu (D. Mubayi) 1. Partially supported by NSF grant DMS 0653946.…”
mentioning
confidence: 76%
See 1 more Smart Citation
“…The case d = k follows from a theorem of Chvátal [5] as it was observed by Chen, Liu, and Wang [4]. Keevash and Mubayi [14] proved Conjecture 1 when both k/n and n/2 − k are bounded away from zero, and Mubayi and Ramadurai [18] for n > n 3 (k).…”
Section: Conjecture 1 Call a Family Of K-setsmentioning
confidence: 81%
“…Chen, Liu and Wang [21] observed that the case k = d + 1 of Conjecture 5.2 is reduced to Conjecture 5.1, which is true by a result of Chvátal.…”
Section: Conjecture 52 (Mubayi [124]) Suppose Thatmentioning
confidence: 91%